2014
DOI: 10.1245/s10434-014-4041-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MRI and CT for Predicting the Peritoneal Cancer Index (PCI) Preoperatively in Patients Being Considered for Cytoreductive Surgical Procedures

Abstract: MRI more accurately predicts PCI preoperatively in patients undergoing evaluation for cytoreductive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
124
1
12

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(142 citation statements)
references
References 16 publications
5
124
1
12
Order By: Relevance
“…Among these, 499 patients from 8 studies have homogenous clinical characteristics and represent the most homogenous population, on which conclusions can be drawn with a higher level of interest. In this population, the median overall survival is 37.3 months (range 27-78), the median disease-free survival is 14.4 months (range [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], and the median 5-year overall survival is 40% (range .…”
Section: Topic 6: What Is the Best Timing As Far As Results Are Concementioning
confidence: 99%
“…Among these, 499 patients from 8 studies have homogenous clinical characteristics and represent the most homogenous population, on which conclusions can be drawn with a higher level of interest. In this population, the median overall survival is 37.3 months (range 27-78), the median disease-free survival is 14.4 months (range [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], and the median 5-year overall survival is 40% (range .…”
Section: Topic 6: What Is the Best Timing As Far As Results Are Concementioning
confidence: 99%
“…Preoperative MRI and CT of the abdomen and pelvis play a critical role in the assessment of the extent of peritoneal and visceral disease in patients being considered for CRS and HIPEC for CPM [48]. In comparison with CT, MRI uses different types of image contrast to create images that are more sensitive for detection of peritoneal lesions [4951].…”
Section: Controversial Issues and Latest Progressmentioning
confidence: 99%
“…With major refinements in hardware and software, functional MRI such as diffusion-weighted MRI (DWI) has become technically possible. Various tumors actuate restricted diffusion of water protons which can be evaluated by DWI, resulting in an area of altered signal on DWI [48]. The sensitivity of DWI for depicting peritoneal tumor has opened the gate to potential advancements in detecting disseminated peritoneal metastatic disease.…”
Section: Controversial Issues and Latest Progressmentioning
confidence: 99%
“…Jiang et al validate a novel tool to measure QOL in patients undergoing isolated limb infusion procedures. 10 Three articles (by Tohme et al, 11 Low et al, 12 and Baumgartner et al. 13 ) are important as they demonstrate the advances being made in the field to better predict our failures.…”
mentioning
confidence: 99%
“…11 The second looks at the utility of novel imaging with magnetic resonance technology to predict more accurately the peritoneal burden of disease. 12 The third looks at predictors of progression after CRS?HIPEC and found that nodal disease was likely the most significant factor. Innovative approaches to the management of patients with peritoneal disease are highlighted further.…”
mentioning
confidence: 99%